Pelindungan Merek Terhadap Penyesatan Afiliasi Merek Dalam Dunia Digital Berdasarkan UU Merek dan UU ITE - Salsabila, Shafa; Ramli, Ahmad M.; Permata, Rika Ratna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of internet technology in Indonesia is on the rise. This aligns with the increasing level of crime due to the lack of boundaries in the digital world. One of these crimes is in the area of trade, where bad-faith business actors often engage in brand affiliation deception. Brand affiliation deception refers to a situation where certain parties piggyback on a genuine brand to create a misleading perception, causing consumers to believe that the two brands are affiliated in business with each other. However, regulations regarding brand affiliation deception are not fully and rigidly outlined in Indonesian legislation. The aim of this study is to examine and determine which legal actions constitute brand affiliation deception in the digital world according to Law Number 20 of 2016 concerning Trademarks and Geographical Indications, and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. Additionally, the study seeks to identify which legal actions can be taken in cases of brand affiliation deception as per Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The research methodology employed is a normative juridical approach, utilizing document studies or literature materials with secondary data comprising primary legal materials, secondary legal materials, and tertiary legal materials. The research results indicate that legal acts of brand affiliation deception in the digital world are classified as trademark violations in the form of passing off and cybersquatting, because brand affiliation deception can create the false assumption that the genuine brand and the piggybacking brand have business relations with each other due to bad faith. Legal actions that can be taken in the event of violations involving brand affiliation deception include filing for damages and/or brand cessation, as well as filing criminal charges as stipulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions.